Psikologi Pendidikan Islam Menurut Ibnu Qayyim Al-Jauziyyah - Yadi, Yadi; Rohimah, Siti (Lembaga Yasin AlSys, 2026)
Islamic educational psychology is a discipline that examines educational processes based on the Islamic view of the nature of the human being, soul, intellect, and heart, and places the spiritual dimension at the core of human development and learning, in contrast to Western educational psychology, which tends to be secular. Within this framework, the thought of Ibn Qayyim al-Jawziyyah (691–751 H) makes an important contribution to understanding human psychology through the concepts of fitrah, qalb, nafs, ʿaql, and tazkiyatun nafs. This article aims to examine scientifically and systematically the concept of Islamic educational psychology according to Ibn Qayyim, including his views on the nature of the human being, the aims of education, the roles of educators and learners, and educational methods that are aligned with psychological development. The research employed a library research method with a descriptive-analytical approach to Ibn Qayyim’s major works. The findings indicate that Ibn Qayyim’s thought is relevant as a foundation for developing a holistic and integrative Islamic education that brings together spiritual, intellectual, and moral dimensions within the educational process and is oriented toward forming individuals who are faithful, knowledgeable, and of noble character. These results affirm that Ibn Qayyim’s concept of Islamic educational psychology can serve as a normative and conceptual reference in formulating a contemporary Islamic educational paradigm that emphasizes balance in the development of spiritual, intellectual, and behavioral potentials.